Coping with large multi-level class in English language learning - Benny Kurnianto (Universitas Islam Malang, 2021)
To improve students’ English proficiency, Indonesian Civil Aviation Institute has placed TOEFL® preparation in the curriculum of study program. Nevertheless, the learning design was not common compared with similar program of TOEFL® preparation in another institution. ICAI put a single teacher in class consisted of 24 students with various skills. Consequently, the English teacher had to employ a strategy to cope with this large multilevel class. This qualitative research was conducted to analyze the teacher’s strategy. Its purpose is to give enlightenment toward the conformity between learning design and learning objectives. A pre-test and post-test were given to a determined class and the grades were compared to see the fulfillment of the objective. An observation and note taking was undertaken during the learning process to explain the strategy. The result shows that the teacher occupy cooperative learning through flexible grouping to cope the class challenge. While the result shows 57% students in the class were able to gain 500 as minimum required score, it has implication in examining the learning design in broader context.Keywords: classroom; multilevel; teacher-students ratio